Canopy Leaf Traits, Basal Area, and Age Predict Functional Patterns of Regenerating Communities in Secondary Subtropical Forests - Müller, Sandra Cristina; Bergamin, Rodrigo Scarton; Bordin, Kauane Maiara; Klipel, Joice; Rosenfield, Milena Fermina (Frontiers in Forests and Global Change, 2021)
Secondary forests originate from natural regeneration after fallow (succession) or restoration. Species assembly in these communities, which can affect ecosystem functions and successional trajectories, is very unpredictable. Trait-based trajectories can shed light on the recovery of ecosystem functions and enable predictions of how the regenerating communities will change with forest age. Regeneration communities are affected by initial conditions and also by canopy structure and functional traits that alter dispersers’ attractiveness and coexistence mechanisms. Here we evaluated how community functional traits change over time and tested if functional diversity and composition of the established canopy, as well as the structure of the canopy and forest age, influence the functional structure of regenerating tree communities when compared to their reference forests. For this, we calculated dissimilarity in trait composition (community-weighted means) and in functional diversity of regenerating communities of each succession/restoration stand, using the tree stratum of nearby mature forests as baseline values. Functional trait information comprises leaf, wood density, and reproductive traits from tree species. Our community data contain information from natural successional forests and restoration sites, in the South-Brazilian Atlantic forest. Predictor variables of functional dissimilarities were forest age, canopy structural variables, canopy functional composition and functional diversity. Results showed leaf traits (leaf dry matter content, leaf nitrogen content, leaf nitrogen-phosphorus ratio) and seed mass varying with forest age. Canopy functional composition based on leaf traits and total basal area significantly predicted multiple trait functional dissimilarity between the regeneration component of secondary forests and their reference community values. Dissimilarity increased when the canopy was composed of species with more acquisitive traits. Difference in functional diversity was only influenced by forest age. Mid-stage secondary forests showed lower functional diversity than early-stage forests. Our results indicated the importance of canopy traits on the natural regeneration of secondary subtropical forests. If functional similarity with reference forests is a desired objective in order to recover ecosystem functions through natural regeneration, leaf functional traits of canopy trees that establish or are planted in degraded areas must be considered in the successional processes.